Assessing Students’ Perception of a YouTube-Based English Learning Resource: A Quantitative Study at MAN 3 Tangerang - Childa Faiza; Viviana Lisma Lestari (Departement of Mathematics Education, 2024)
The aim of this study was to find out how MAN 3 Tangerang students felt about YouTube videos that were utilized as a English learning resource. A quantitative descriptive research method is employed. An adapted questionnaire was used to collect data for this study utilizing the questionnaire method. Three indicators make up the questionnaire: media practicality, media usability, and accessibility. After that, the research data are examined utilizing the percentation statistical formula. Based on the data analysis results, it is known that students' opinions on English learning materials based on YouTube videos fall into the excellent category, scoring 80 of the total indicators.